The Myth of the Rumah Tusuk Sate in Chinese Culture from a Christian Perspective - Johanes Kurniawan; Thomas Pentury (Global Writing Academica Researching & Publishing, 2023)
A home is the most comfortable dwelling for a family. Unfortunately, it can be influenced by cultural elements, traditions, and myths that bring about unfavorable beliefs. Many assumptions argue that the 'Rumah Tusuk Sate' (House of Satay Skewers) is an uncomfortable place to live due to the negative impacts it may bring, driven by cultural perspectives, traditions, religious beliefs, and Feng Shui among the Chinese community. These beliefs are deeply rooted in culture and traditions, passed down through stories linked to myths. This research aims to explore the underlying causes of cultural factors that influence the perception of 'Rumah Tusuk Sate' from a Christian perspective. This study employs a qualitative method, using library research as the primary source of data, encompassing books such as the Bible, articles, and literature. The Bible, from a Christian perspective, firmly addresses questions regarding the cultural influence on the perception of 'Rumah Tusuk Sate.' Christianity and culture can coexist harmoniously without altering the fundamental concept of faith grounded in the pure Gospel.